The Landau–Lifshitz equation in atomistic models - Ellis, M.O.A.; Evans, R.F.L.; Ostler, T.A.; Barker, J.; Atxitia, U.; Chubykalo-Fesenko, O.; Chantrell, R.W. (Физика низких температур, 2015)
The Landau–Lifshitz (LL) equation, originally proposed at the macrospin level, is increasingly used in Atomistic
Spin Dynamic (ASD) models. These models are based on a spin Hamiltonian featuring atomic spins of
fixed length, with the exchange introduced using the Heisenberg formalism. ASD models are proving a powerful
approach to the fundamental understanding of ultrafast magnetization dynamics, including the prediction of the
thermally induced magnetization switching phenomenon in which the magnetization is reversed using an ultrafast
laser pulse in the absence of an externally applied field. This paper outlines the ASD model approach and
considers the role and limitations of the LL equation in this context.